Study on Market Situation and Management Specifications of Short-Range Radio Communication Devices - Xiaobo Wang; Qizhu Song; Junfeng Wang; Hongbo Tao; Xiaoyong Liu; Xinhao Liu (Dianxin kexue)
Micro-power（short-range radio communication）wireless devices are widely used, and numerous, they play a more and more important role in people's daily life. But there are still some problems in its supervision and administration, the market situation is also chaotic. The management status of the micro-power equipment was analyzed, and some market surveys were made. The problems and issues for micro-power radio equipment in the supervision were summarized. Finally some countermeasures and suggestions were put forward.